2009
DOI: 10.1186/1477-7517-6-32
|View full text |Cite
|
Sign up to set email alerts
|

Integrated programs for women with substance use issues and their children: a qualitative meta-synthesis of processes and outcomes

Abstract: BackgroundThere is a need for services that effectively and comprehensively address the complex needs of women with substance use issues and their children. A growing body of literature supports the relevance of integrated treatment programs that offer a wide range of services in centralized settings. Quantitative studies suggest that these programs are associated with positive outcomes. A qualitative meta-synthesis was conducted to provide insight into the processes that contribute to recovery in integrated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 67 publications
(222 reference statements)
5
65
0
4
Order By: Relevance
“…Falkin and Strauss (2003) found that one in five women in their study reported that their children had helped them to stop substance use. A meta synthesis of existing research on women with substance use disorders and parenting (Sword et al, 2009) reported that children often exert a motivating presence and a sense of security and comfort, along with a sense of urgency to work on recovery issues.…”
Section: Discussionmentioning
confidence: 99%
“…Falkin and Strauss (2003) found that one in five women in their study reported that their children had helped them to stop substance use. A meta synthesis of existing research on women with substance use disorders and parenting (Sword et al, 2009) reported that children often exert a motivating presence and a sense of security and comfort, along with a sense of urgency to work on recovery issues.…”
Section: Discussionmentioning
confidence: 99%
“…Being pregnant at treatment entry increased the odds of success. For some women pregnancy may signify a change in social role responsibilities that promotes drug use cessation and sustained recovery (Massey et al., 2012; Sword et al, 2009; Mitchell et al, 2008; Massey et al, 2011). For others, potential involvement with the social service and child welfare systems, along with child custody concerns, can exert enormous pressures on pregnant women to quit using drugs (Cloud and Granfield, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…La documentation tant clinique que scientifique souligne l'importance des attitudes professionnelles positives à l'égard des futures et nouvelles mères ainsi que des actions visant le renforcement du pouvoir d'agir pour lever les obstacles auxquels se heurte ce groupe de femmes, comme la peur de ne pas être à la hauteur de leur nouveau rôle de mères et la faible estime de soi 24,34 . Parmi les attitudes des intervenantes jugées aidantes par les participantes de la présente étude, retenons en particulier la reconnaissance de leurs forces, l'encouragement, l'absence de jugement porté sur leur situation, le respect ainsi que l'écoute à l'égard de ce qu'elles souhaitent pour elles et leur enfant.…”
Section: Discussionunclassified
“…Parmi les manifestations de ce type de changements, retenons en particulier un rapprochement avec leur famille, des rapports plus positifs avec les intervenants sociaux et une plus grande utilisation des ressources d'aide. Les recherches soulignent que les interventions qui ont le plus de succès auprès de ce groupe de population sont celles qui adoptent une approche globale pour répondre aux besoins complexes et diversifiés de ces femmes 31,34,36 . Cela est d'autant plus important que les contacts précoces et réguliers avec les services augmentent les gains et aident à diminuer les risques de séquelles pour les enfants 39 .…”
Section: Discussionunclassified